2014
DOI: 10.1063/1.4904078
|View full text |Cite
|
Sign up to set email alerts
|

Time- and power-dependent operation of a parametric spin-wave amplifier

Abstract: We present the experimental observation of the localized amplification of externally excited, propagating spin waves in a transversely in-plane magnetized Ni81Fe19 magnonic waveguide by means of parallel pumping. By employing microfocussed Brillouin light scattering spectroscopy, we analyze the dependency of the amplification on the applied pumping power and on the delay between the input spin-wave packet and the pumping pulse. We show that there are two different operation regimes: At large pumping powers, th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 17 publications
0
24
0
1
Order By: Relevance
“…An example for time-resolved BLS microscopy can be found in Brächer et al [124]. In this experiment, Brächer et al demonstrated the active amplification of propagating spin waves in a Ni 81 Fe 19 waveguide using parametric pumping.…”
Section: Temporal Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…An example for time-resolved BLS microscopy can be found in Brächer et al [124]. In this experiment, Brächer et al demonstrated the active amplification of propagating spin waves in a Ni 81 Fe 19 waveguide using parametric pumping.…”
Section: Temporal Analysismentioning
confidence: 99%
“…(B) Time-resolved BLS measurement of spin-wave pulses amplified via parametric pumping in a microstructured Ni 81 Fe 19 waveguide [124].…”
Section: Figure 15 | (A)mentioning
confidence: 99%
“…The notable difference of the intensity in front of the amplifier by about ±35% is likely mediated due to the interference of the incoming signal spin waves with spin waves reflected during their propagation past the amplifier or with spin waves created by a weak amplification of counterpropagating waves. For completeness, the red circles show the intensity arising if only parallel pumping is applied, which leads to the amplification of thermal spin waves, a process known as parametric generation363839. As can be seen from the figure, for the given pumping power and pulse duration, no rise of the BLS intensity within the amplifier due to parametric generation is noticeable.…”
Section: Demonstration Of the Phase-to-intensity Conversionmentioning
confidence: 99%
“…This leads to a strong spatial localization of the pumping process which provides the needed effective wave vector k p . Thus, this region is the actual local parametric amplifier3637.…”
Section: Demonstration Of the Phase-to-intensity Conversionmentioning
confidence: 99%
“…Consequently, the losses of the resonator are dominated by the propagation loss. In order to counteract these losses, we employ parametric amplification, also known as parallel pumping [16][17][18][19] . In this technique, the system is pumped at the frequency f p which equals twice the resonance frequency f .…”
Section: Layout and Working Principlementioning
confidence: 99%